Building Geological Model for Tertiary Reservoir of Exploration Ismail Oil Field, North Iraq - Hamdulla, Sameera M.; Hassan, Aboosh H.; Tawfiq, Yahya Jarjees (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Geologic modeling is the art of constructing a structural and stratigraphic model of a reservoir from analyses and interpretations of seismic data, log data, core data, etc. ‎[1].   A static reservoir model typically involves four main stages, these stages are Structural modeling, Stratigraphic modeling, Lithological modeling and Petrophysical modeling ‎[2].   Ismail field is exploration structure, located in the north Iraq, about 55 km north-west of Kirkuk city, to the north-west of the Bai Hassan field, the distance between the Bai Hassan field and Ismael field is about one kilometer ‎[3].   Tertiary period reservoir sequences (Main Limestone), which comprise many economically important units particularly reservoir pay zone, in Ismail field are belong to middle Miocene age and Oligocene age, which includes six formations, Jeribe, Bajwan, Baba, Baba/palani and Palani formation.   The information of Ismail field such as final well report, drill stem test, completion test and well logs data also previous studies and results of core data, indicated that hydrocarbons are accumulated in the Baba formation.   The main purpose of this study is to make use of all the available sets of data acquired from Ismail field to build a static geological model for Baba formation in Ismail field to get full description for this reservoir.